Development of a Cost Effective Power Generation System: An Overview - Shiv Prakash Bihari; Yogita Kumari; Bhupender Sehgal; R.N. Chaubey; Anmol Gupta (IAES Indonesian Section, 2016)
This paper presents an overview on development of cost effective power generation system and motivates for development of a model for hybrid system with wind to investigate the combined operation of wind with different sources to cater to wind’s stochastic nature for imbalance minimization and optimal operation. Development of model for trading power in competitive electricity market and development of strategies for trading in electricity markets (wind energy and reserves markets) to investigate the effects of real time pricing tariffs on electricity market operation has been illustrated in this paper. Dynamic modelling related studies to investigate the wind generator’s kinetic energy for primary frequency support using simulink and simulation studies on doubly fed induction generator to study its capability during small disturbances / fluctuations on power system have been described.